The influence of financial literacy, financial attitudes, and lifestyle on financial behavior - Adhi Widyakto; Ziyana Wahyu Liyana; Tri Rinawati (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
This study aims to examine the effect of financial literacy, attitudes, and lifestyle on financial behavior in Management students of the Faculty of Economics, class of employees at the University of Semarang, class of 2019/2020. The population in this study were active students majoring in employee class management in the odd semester class of 2019/2020. The sample in this study was purposive sampling method. Purposive sampling is a data sampling technique based on certain considerations. The sample in this study collected 123 respondents. This research uses quantitative data type and the data source used is primary data. The data analysis technique using regression analysis test was carried out with the help of SPSS version 25. The results showed that only financial attitudes had a significant positive effect on financial behavior, while other variables such as financial literacy and lifestyle had no a significant effect on financial behavior. Its mean that financial attitudes will improve the quality of financial behavior in students.